Bird Lake moon - Henkes, Kevin (Greenwillow Books, 2008)
Twelve-year-old Mitch, spending the summer with his grandparents at Bird Lake after his parents' separation, becomes friends with ten-year-old Spencer, who has returned with his family to the lake where his little brother drowned years earlier, and as the boys spend time together and their friendship grows, each of them begins to heal.